Music and its influence - Hofer, Henrietta M. (My University, 1902)
Introduction: Music is the most beautiful-and inspiring-gift of God, to all the world below. It is as Emile Frances Bauer has so fittingly defined it “a vehicle in which to carry such emotions, thoughts, and sentiments as are too vast, too deep, too great for words. Musical study is not enough. After having this magnificent vehicle one must have thoughts, emotions, and sentiments that deserve to ride in such state.” What is a home without music? It is barren and unhappy. Music is soul inspiring; it makes the home happy; it keeps the children at home; it strengthens character; gives great enjoyment for entertainments; and cheers the sick.
Citation: Hofer, Henrietta M. Music and its influence. Senior thesis, Kansas State Agricultural College, 1902.
Morse Department of Special Collections
Keywords: Music; Theses; Manuscripts (documents)